The Correlation Between Online Game Addiction and Learning Motivation of Class VII Students at Mts Negeri 1 South Jakarta - Lopulalan, Frisangel; Dinaryanti, Ratna Sari; Rostarina, Nila; Ramadhan, Gaung Eka (Asosiasi Dosen Muda Indonesia, 2026)
Online gaming has become increasingly popular among adolescents, and its interactive features may encourage prolonged use that can develop into gaming addiction, potentially disrupting academic engagement and reducing learning motivation. Objective: This study aims to examine the relationship between online game addiction and students’ learning motivation among grade 7 students at MTs Negeri 1 South Jakarta. Methodology: This research employed a quantitative cross-sectional design. Data were collected from grade 7 students at MTs Negeri 1 South Jakarta and analyzed using the chi-square statistical test to assess the association between online game addiction and learning motivation. Findings: The results showed a statistically significant relationship between online game addiction and learning motivation (p = 0.001 < 0.05), indicating that higher levels of online game addiction are associated with lower learning motivation. Implications: These findings suggest the importance of school-based educational interventions and awareness programs involving students, parents, and educators to prevent excessive gaming and to support students’ academic motivation. Originality: This study provides empirical evidence in an Indonesian junior secondary school context, offering practical insights for designing targeted prevention strategies and supporting further research on behavioral factors influencing learning motivation.